Posted by
**Zoe** on
.

Use the expressions for left and right sums and the table below.

right-hand sum = summation (n above and i =1 on the bottom) f(ti) * change in t = f(t1) * change in t + f(t2) * change in t + .... + f (tn) * change in t

left-hand sum = summation (n above and i = 0 on the bottom) f(ti) * change in t = f (t0) * change in t + f (t1) * change in t + ... = f (tn - 1) * change in t.

Table: t 0 4 8 12 16

f (t) 26 24 23 21 18

If the table messed up, the points are (0, 26), (4, 24) , (8, 23) , (12, 21), (16, 18)

a.) If n = 4, what is change in t? What are t0, t1, t2, t3, t4? What are f (t0), f (t1), f (t2), f (t3), f(t4)?

t0= f (t0) =

t1 = f (t1) =

t2 = f (t2) =

t3 = f (t3) =

t4 = f (t4) =

b.) Find the left and right sums using n = 4.

Left sum =

Right sum =

c.) If n = 2, what is change in t? What are t0, t1, t2? What are f (t0), f (t1), f(t2)?

t0 = f (t0) =

t1 = f (t1) =

t2 = f (t2) =

d.) Find the left and right sums using n = 2

Left sum =

Right sum =

Please show work and explain. I have no idea where to start from.